KETERAMPILAN MEMBUAT KERUPUK OPAK BAGI ANAK TUNAGRAHITA SEDANG MELALUI PENDEKATAN KOOPERATIF TIPE STAD - Jasni - Jasni (Jurnal Penelitian Pendidikan Khusus, 2013)
The background of this research is the discovery of six adult mental retardation class VII student who had difficulty in grinding cassava cracker-making processes opaque, it is Because The classroom teacher can not Convey the subject matter appropriate for the needs of children and the teacher only The demonstration uses the method to provide eye learning skills, thus making the children Often Become forget or less understand what the teacher explained. In other conditions in the milling process sweet child has difficulty pushing tool grinder, mill thickness child has not reached 0.5 mm. The purpose of this research is to improve the ability to grind cassava through the application type STAD cooperative approach when teaching children skills for mental retardation was a class VII. This pebelitian type is action research class (classroom action research) that takes the form of collaboration. These actions were taken to six children, mental retardation was a class VII in SLB YAPEM Tarusan. The results Showed for the first cycle of six sessions held in the learning process that starts from introducing the tools, setting tools, grinding cassava and assessment of the work of children. Based on the average value obtained by the students at the end of the first cycle can be seen that the W after the given action I got 50%, the S gets a value of 50%, T gets the value of 40%, a gain value of 40%, R gets the value of 50%, and Kalsogot50%. The results of the second cycle Showed an increasing ability of the child. Where W after being given a second act gets a score of 70%, the S gets the value of 80%, T gets the value of 60%, a gain value of 60%, the R gets a score of 70%, and K got 60%. From the results presentation and analysis of the data it can be concluded that the use of type STAD cooperative approach to improve the ability to grind cassava crackers opaque making skills for mental retardation children were class VII. Thus suggested to the schools, teachers, and Researchers can use the following for a cooperative approach to improve learning skills for children tunagrahita being.